ORAL MANIFESTATIONS OF BRONCHIAL ASTHMA - R. JAYASRIKRUPAA; K.M.K.MASTHAN; N.ARAVINDHA BABU; M.ELUMALAI (International Journal of Pharma and Bio Sciences, 2014)
The aim of this study was to ascertain the hard tissue changes and mucosal changes in the oral cavity of bronchial asthma patients. Effect of the drugs of varied treatment protocol on the oral tissues was also correlated with the oral manifestations. A random study was conducted among 100 bronchial asthma patients (51 females and 49 males patients of all age groups and socio economic status were included). All bronchial asthma patients were under treatment depending on degree of disease condition. Data was analyzed statistically for students T test (by SPSS 11.5 software application). Oral mucosal changes predominantly Oropharyngeal candidiasis, ulcer, gingivitis, periodontitis and hard tissue changes in the oral cavity such as dental caries, erosion were clinically observed. Significant association was evident between the drugs used in bronchial asthma treatment, disease progression on the oral hard tissue and mucosal changes.